Sustainability in Orthodontics: what can we do to save our planet? - Matheus Melo Pithon; Lucianne Cople Maia de Faria; Orlando Motohiro Tanaka; Antônio Carlos de Oliveira Ruellas; Laura Salignac de Souza Guimarães Primo
ABSTRACT The sustainability of the natural resources of our planet is a topic for worldwide debate. Mankind, during its evolution as a species, has not been greatly concerned about conserving the environment in which we live. Nowadays we are reaping the fruits of this neglect. Climatic changes and storms are good examples of this. We, humans, must re-think our attitudes in order to leave the planet in a healthy state to be used by our descendants. But thinking of orthodontics, what can we do as orthodontists? From this perspective, the authors of the present study aimed, in a clear and objective manner, to present simple and sustainable ways to proceed during our activity as orthodontists, in order to minimize the effects on nature, caused by man.